Playing the game: explaining how Luxembourg has responded to the Networked Readiness Index. Issue 4 (12th June 2017) - Binsfeld, Nico; Whalley, Jason; Pugalis, Lee
Abstract : Purpose: Over the past decade or so, successive Luxembourgish governments have sought to develop the country's information and communication technologies (ICT) sector. In this paper, the authors will aim to examine how Luxembourg's relative position in the "Networked Readiness Index" (NRI), a key international benchmarking exercise published by the World Economic Forum, has evolved over time as these ambitions have been achieved. The paper also explores what policy initiatives could be implemented to further improve Luxembourg's ranking in the NRI. Design/methodology/approach: A longitudinal case study-based approach, drawing on secondary data and the annual publication of the NRI between 2003 and 2016, was adopted. Findings: Luxembourg's position in the NRI has improved from 27th in 2003, so that it now ranks among the top ten countries in the world. In particular, Luxembourg has substantially improved its position with regards to "infrastructure" and "international connectivity". However, there are also areas, mainly linked to education, the provision of human resources and policies that allow for and stimulate entrepreneurship where further improvements appear possible. Social implications: The paper highlights the need for an overall, holistic, ICT development strategy. Such a strategy would cover not only cover infrastructural and technical aspects but also educational, social, regulatory and economic issues as well. Originality/value: The paper charts the evolution over time of Luxembourg's position in an important international ICT index and identifies its current strengths and weaknesses in terms of the different elements that constitute the NRI. This paper represents the first attempt to investigate the position of a small country, which are often overlooked in the literature, in terms of its changing position and the policies developed and enacted by a national government.